A dual-drug strategy to enhance the function of cryopreserved ovaries by promoting revascularization and inhibiting follicle over-activation - Lingyu Li; Jian Yang; Longzhong Jia; Jing Liang; Kaixin Cheng; Xuebing Yang; Lu Mu; Ge Wang; Kaiying Geng; Qiuxian Hu; Xueqiang Xu; Zhen Li; et al. (Reproductive Biology and Endocrinology)
Abstract Background Ovarian tissue cryopreservation and transplantation (OTCT) is a promising approach for fertility preservation. However, significant follicle loss after transplantation challenges long-term reproductive recovery. Although primordial follicle loss and ischemic damage are known contributors, the underlying mechanisms and effective strategies to mitigate these damages are still lacking. Methods Ovarian tissues from wild-type or Tek-CreER T2 ;mTmG female mice were cryopreserved using vitrification. Follicle dynamics after OTCT were analyzed through histology, proteomics, and high-resolution imaging. To assess protective effects, cryopreserved ovaries were treated with 500 nM rapamycin (Rapa), an inhibitor of primordial follicle activation; 5 ng/mL vascular endothelial growth factor A (VEGFA), which promotes angiogenesis; or both (Cryo + VRCS, VEGFA-Rapa Combination Strategy). DMSO or H2O served as controls. Grafts were collected at 3, 7, 14, and 120 days post-transplantation, with measurements of vascular density, tip cell density, follicle activation, and remaining follicles. Oocyte quality was evaluated via in vitro fertilization, and graft lifespan was estimated through estrous cycle monitoring. Results Our study observed a rapid decline in follicle numbers shortly after transplantation in a mouse model. Proteomic analysis and high-resolution 3D imaging revealed that this depletion was primarily due to damage to tip cells, which are crucial for angiogenesis, and the overactivation of dormant primordial follicles. Damage to tip cells compromised vascular reconstruction, leading to ischemic injury, while mechanical handling during tissue isolation and cryopreservation triggered excessive follicle activation. We implemented a combination therapy using rapamycin to inhibit follicle activation and VEGFA to promote angiogenesis prior to transplantation. This approach significantly improved follicle survival, extended reproductive function, and enhanced oocyte quality. Conclusion Our study provides a practical strategy for preserving the reproductive potential of cryopreserved ovarian tissues by simultaneously targeting vascular integrity and follicle stability through the dual drug strategy of VEGFA and rapamycin combine treatment.